Morphology of the syrinx of three species of birds from Brazilian cerrado (Psittacara leucophthalmus, Rhynchotus rufescens and Cariama cristata): Gross anatomy and light microscopy study - Oliveira, Elton Luis Ritir [UNESP]; Zuliani, Fernanda [UNESP]; de Camargo, Gabriel Corrêa [UNESP]; Desantis, Salvatore; Schimming, Bruno Cesar [UNESP] (Wiley, 2023)
The aim of this study was to describe the morphology of the trachea and syrinx at macroscopic and light microscopy levels of three species of birds from different orders that inhabit the Brazilian cerrado. For that, five adult specimens (three males and two females of each species) of white-eyed parakeet (Psittacara leucophthalmus), red-winged tinamou (Rhynchotus rufescens) and red-legged seriema (Cariama cristata) were used. The trachea and syrinx of the birds were collected and destined for anatomical and histological studies. The trachea of the studied birds presented an elongated path and originated in the larynx and extended caudally to the syrinx. No sexual dimorphism was observed in the syrinx of the studied species, probably because it is associated with their song, which is very similar between males and females of these species. The findings of this study allowed us to classify the syrinx as tracheal in the white-eyed parakeet and tracheobronchial in the red-winged tinamou and red-legged seriema. In general, the morphological features of the trachea and syrinx were similar to those described for other species of birds, such as the presence of intrinsic and extrinsic syringeal muscles, and the lateral and medial tympaniform membranes, which would represent important anatomical structures in sound production through vibration during expiration and eventual inspiration. The morphological structure of the syrinx in the three avian species of the Brazilian cerrado is consistent with the ability of these avian species to perform a potential vocalization, especially the red-legged seriema that emits characteristic sounds very loud and can carry several kilometres.
Keywords: birds; histology; red-legged seriema; red-winged tinamou; syrinx; white-eyed parakeet